Mean Platelet Volume as a Predictive Marker for Poor Prognosis of Acute Renal Failure in children - Yousefichaijan, Parsa; Eghbali, Aziz; Rafiei, Mohammad; Taherahmadi, Hassan; Shariatmadari, Fakhreddin; Alinejad, Saed; Ghandi, Yazdan; Naziri, Mahdyieh (Journal of Pediatric Nephrology, 2015)
Introduction: Acute renal failure (ARF) is a clinical syndrome in which a sudden deterioration in renal function results in the inability of the kidneys to maintain fluid and electrolyte homeostasis. A classification system has been proposed to standardize the definition of acute kidney injury in adults. These criteria of risk, injury, failure, loss and end-stage renal disease were given the acronym of RIFLE. Our goal was to study the mean platelet volume (MPV) as a prognostic predictor of ARF in children. Mean platelet volume (MPV) is a machine-calculated measurement of the average size of platelets in blood and typically included in blood tests as part of CBC (Complete Blood Count). Since the average platelet size is larger when the body is producing increased numbers of platelets, MPV can be used to make inferences about platelet production in bone marrow or platelet destruction problems. Material and Methods: The records of 200 patients with ARF were investigated prospectively. Complete blood count including MPV, erythrocyte sedimentation rate, serum C-reactive protein and electrolytes of patients were measured and compared. Results: MPV values were low in loss (p=0.0012) and failure (p<0.005). The sensitivity and specificity of MPV for the diagnosis of loss and failure were higher than those of the other inflammation markers. MPV<8.2 fL was significantly associated with poor prognosis in renal functions. Conclusions: MPV is a fast and reliable measurement with considerable predictive value for prediction of prognosis in acute renal failure. Keywords: Acute Kidney Injury; Mean Platelet Volume; Blood Platelets; Acute Kidney Injury; Prognosis.